2016
DOI: 10.1111/ejn.13396
|View full text |Cite
|
Sign up to set email alerts
|

Pathological gambling in Parkinson's disease: what are the risk factors and what is the role of impulsivity?

Abstract: The incidence of pathological gambling in Parkinson's patients is significantly greater than in the general population. A correlation has been observed between dopamine agonist medication and the development of pathological gambling. However, scientists conjecture that the affected patients have underlying risk factors. Studies analysing Parkinson's patients have detected that patients who developed pathological gambling are younger, score higher on novelty-seeking tests, are more impulsive and are more likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 67 publications
1
21
0
2
Order By: Relevance
“…These consequences are also described as correlated with iatrogenic causes: for instance, some pharmacologic treatments of Parkinson's disease may induce gambling, which is related to the altered distribution of dopamine in the above-mentioned areas (Heiden et al, 2017). This alteration determines a strong hedonistic feeling correlated to the habit of gambling which is an integral part of maintaining such a bad habit.…”
Section: From Neurophysiology To Neuropathology: the Establishment Ofmentioning
confidence: 99%
“…These consequences are also described as correlated with iatrogenic causes: for instance, some pharmacologic treatments of Parkinson's disease may induce gambling, which is related to the altered distribution of dopamine in the above-mentioned areas (Heiden et al, 2017). This alteration determines a strong hedonistic feeling correlated to the habit of gambling which is an integral part of maintaining such a bad habit.…”
Section: From Neurophysiology To Neuropathology: the Establishment Ofmentioning
confidence: 99%
“…Studies of risk factors for ICD suggest that a family history of alcoholism may place a PD individual at risk for this behavior. 79 One biological reason for this is alteration to serotonin levels, as reduced levels of tryptophan, an amino acid necessary for making serotonin, is associated with alcoholism. Individuals with low levels of the serotonin (5-HT) metabolite, HIAA, have greater impulsivity characteristics and early signs of alcoholism.…”
Section: Managing Pd-icd Patientsmentioning
confidence: 99%
“…Finally, a current revision work (Heiden, Heinz, & RomanczukSeiferth, 2017) confirmed the higher comorbidity of gambling disorder in pd patients compared to the general population. Some of the factors that explained this comorbidity were dopamine agonist medication, age (younger), higher scores in novelty seeking and impulsivity scales, history of substance abuse disorder (alcohol), genetic mutations, increased functional activation in the mesolimbic reward system, increased dopamine release in the mesolimbic reward system and distorted learning processes (Heiden et al, 2017).…”
Section: Description Of Gambling Disorder: Characteristics and Comorbmentioning
confidence: 99%
“…On the other hand, other revisions confirmed that the incidence of gambling disorder in pd sufferers was higher than that found in the general population. Some of the factors that explained this tendency were dopamine agonist medication, age (younger), marked novelty seeking and impulsivity, background of alcohol use disorder, diverse genetic mutations (N-methyl D-aspartate receptor subtype 2B, dopamine receptor D3, and serotonin-transporter-linked polymorphic region), augmented functional activation in the mesolimbic reward system, augmented dopamine release in the mesolimbic reward system, and distorted learning processes (Heiden et al, 2017). Other revision (meta-analysis) confirmed that patients with pd following dopamine medication denoted disruption in the Iowa Gambling Task performance compared to controls (Evens, Hoefler, Biber, & Lueken, 2016).…”
Section: Gambling Disorder and Pdmentioning
confidence: 99%